(3GdUMGM aj GddZIs - (3ESeGYjd Hf MeGO GdLhgQj , CHh fUQ, J (B393 (3g` s ((3Ydi Hf eMeO Hf YeQ GdYdbei s)
(3ChdgG (B:s
(3GdMeO ddg TcQkG Ydi fhGdg CeG HYO aEfi ChOYJ gPG GdcJGH eGUM YfOi ef gPg GddZI GdJi TQagG Gddg efRdJgG s
(3BNQgG (B:s
(3bGd Ph GdQeI (B: (3GdGjG GSdei jG OGQei Ydi GdHdi hdG RGd efgdG HMQ Ydjc GdbWQ GfJgi cJGH GdUMGM s
(3GdfSNI HgG MhGTs
(3YdjgG JedcGJs
(3cJHJ HNW ajg HYV GdVHW s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs